Efficiency Assessment of Regional Social and Demographic Process Management: Global Trends and Regional Specifics - Elena Vasilyeva (European Regional Science Association (ERSA), 2013)
The problem of management of regional social and demographic process becomes the most actual whereas its consideration through the lenses of global trends (small number of children in a nuclear family, higher life expectancy rate, objective ageing of the population). This population reproduction level is an irreversible consequence of the urbanization processes and entrance into the phase of postindustrial development. Nevertheless, this is not to say that management of regional social and demographic process is impossible. It indicates that there are limits of management opportunities. The irreversible nature of this change is more or less typical for all regions; however, it should not be reduced to a single direction of social and demographic change in the regions. Spatial differentiation and extremely unbalanced social and economic development of the Russian regions have a significant effect both on the social and demographic situation, and on the development of the respective management tools. The problem of management of regional social and demographic process lies in acceptance of the irreversible nature, and in taking into account of simultaneous impact of the global trends and regional specifics on social and demographic processes. In this connection, the research objective is identification of social and demographic processes which are in the social and demographic global trend line and its deviations that the efficiency of management of regional social and demographic process is assessed. This paper presents methodology for assessment of efficiency of the social and demographic processes management on a regional level. The methodology is based on indicative analysis techniques and procedures. Since the development of any management techniques recommendations should be based on a clear understanding of the nature of social and demographic processes in the region, this methodology also addresses the task of identification of social and demographic processes following the global reproduction of population trends, as well as any variations from these trends. In addition, for the purposes of assessing efficiency of management of social and demographic processes in the region, the authors recommend monitoring the amounts of financing of the socially significant budget items, which would provide a tool for rationalizing the investment requirements for the specific social and demographic projects. This paper presents the results of the methodology approbation in the Ural Federal District.
Keywords: R53; R58; J11; J18; 330; Social and demographic processes; management efficiency; region; social and demographic transformations and anomalies; socially significant budget items; indicative analysis; methodology